2016
DOI: 10.1097/md.0000000000004340
|View full text |Cite
|
Sign up to set email alerts
|

Obturator internus pyomyositis manifested as sciatica in a patient with subacute bacterial endocarditis

Abstract: Pyomyositis is a pyogenic infection of the skeletal muscles causing myalgia and fever in patients. Hematogenous seeding engendered by persistent bacteremia and septic embolism is usually the underlying cause of the disease. Trauma, intravenous drug use, and immunodeficiency are the main predisposing factors.Obturator internus pyomyositis with sciatica has not previously been reported. We report a rare case of a patient with subacute bacterial endocarditis presenting with left buttock pain and sciatica.Computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 14 Our patient also suffered from recurrent bacterial pyomyositis in her legs after total hysterectomy and intermittent use of antibiotics, which we believe may have been the primary focus of infection. Although recent reports have shown that S. haemolyticus can cause endocarditis, 2 , 3 they did not reveal short-term IIA or SAH. The case presented here suggests that S. haemolyticus endocarditis might induce the development of IIA and SAH.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“… 14 Our patient also suffered from recurrent bacterial pyomyositis in her legs after total hysterectomy and intermittent use of antibiotics, which we believe may have been the primary focus of infection. Although recent reports have shown that S. haemolyticus can cause endocarditis, 2 , 3 they did not reveal short-term IIA or SAH. The case presented here suggests that S. haemolyticus endocarditis might induce the development of IIA and SAH.…”
Section: Discussionmentioning
confidence: 70%
“…Although Staphylococcus haemolyticus , a coagulase-negative staphylococcus, was previously considered to be weakly virulent, recent reports indicated that S. haemolyticus can cause IE. 2 , 3 Recent data have demonstrated that coagulase negative staphylococci are responsible for 8% of all cases of native valve endocarditis, resulting in a 25% mortality rate, and that methicillin-resistant isolates cause 60% of prosthetic valve endocarditis cases. 4 However, data on IIA following S. haemolyticus IE are still lacking.…”
Section: Introductionmentioning
confidence: 99%